1996
DOI: 10.30843/nzpp.1996.49.11456
|View full text |Cite
|
Sign up to set email alerts
|

Circadian pattern of oviposition in the parasitoids <i>Microctonus aethiopoides</i> Loan and <i>M. hyperodae </i>Loan (Hymenoptera: Braconidae), in relation to host activity

Abstract: Laboratory experiments were carried out to investigate the circadian patterns of oviposition of the parasitoids Microctonus aethiopoides Loan and M. hyperodae Loan in their respective hosts Sitona discoideus Gyllenhal and Listronotus bonariensis (Kuschel). Successful oviposition by M. aethiopoides in S. discoideus occurred more frequently during light than during dark periods, but M. hyperodae achieved higher parasitism levels in L. bonariensis during hours of darkness than during light. Circadian parasitoid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Ferguson et al (1994) suggested that parasitising non-target weevils may provide a 'refuge' and help M. aethiopoides to survive between generations of its target host. Armstrong et al (1996) found that M. aethiopoides oviposited in S. discoideus, primarily during light periods. However, when exposed to L. bonariensis, which feeds during dark periods, but oviposits during the night and day, M. aethiopoides oviposition occurred equally during light and dark periods.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Ferguson et al (1994) suggested that parasitising non-target weevils may provide a 'refuge' and help M. aethiopoides to survive between generations of its target host. Armstrong et al (1996) found that M. aethiopoides oviposited in S. discoideus, primarily during light periods. However, when exposed to L. bonariensis, which feeds during dark periods, but oviposits during the night and day, M. aethiopoides oviposition occurred equally during light and dark periods.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, M. hyperodae (an introduced biological control agent for L. bonariensis (Goldson et al 1984)) laid fewer eggs within its host during the day than the night, possibly indicating a more distinct rhythmicity in stalking activity (Armstrong et al 1996). Several hymenopteran egg and larval parasitoids have distinct circadian rhythms of locomotor activity independent of host activity but this varies with species, sex and strain (Fleury et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the comparatively low levels of parasitism of L. bonariensis by M. aethiopoides suggest that behavioural acceptability may be low. This is perhaps due to a disparity in circadian activity patterns between the parasitoid and the novel host L. bonariensis (Armstrong et al 1996) which is expressed strongly in the field but attenuated under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Field densities of adult parasitoids cannot be reliably estimated from this sampling method. Sampling was always conducted during daylight, usually between midday and 15:00 h. Most M. hyperodae oviposition occurs between dusk and dawn (Armstrong et al, 1996), thus M. hyperodae egg loads were unlikely to substantively decline during daylight hours.…”
Section: Samplingmentioning
confidence: 99%